Penegakan Hukum Bagi Pelaku Tindak Pidana Incest Terhadap Anak di Bawah Umur dalam Perspektif Hukum Pidana Positif dan Hukum Pidana Islam - Marluga Tambunan, Unjur; Mahfudz Harahap, Mar'ie (LPPM Universitas Ekasakti Padang, 2023)
This research discusses law enforcement for perpetrators of sexual relations between individuals who still have familial relationships based on consanguinity in the perspective of positive criminal law and Islamic criminal law. By using a comparative approach method, the researcher found differences between positive criminal law and Islamic criminal law in the process of consanguineous sexual relations, especially in the complaint process, and also in the withdrawal of reports. The researcher categorizes consanguineous sexual relations as adultery, which can be legally processed after a complaint from the victim based on Article 284 paragraph (2) of the Indonesian Criminal Code (KUHP), while in Islamic law, with just one of the three existing pieces of evidence, punishment can be imposed immediately without a complaint. Furthermore, in Article 284 paragraph (4) of the Indonesian Criminal Code (KUHP), it is also stated that the complainant is allowed to withdraw their report before a judge's decision. This is different from Islamic law, where once consensual sexual relations are known to have occurred, the punishment cannot be revoked. Since consensual sexual relations are categorized as adultery, punishment is already stipulated in Islamic law as the absolute right of Allah and has been determined in the Quran. Article 294 of the Indonesian Criminal Code should be amended promptly to prevent weakness and be more effective and precise in preventing and punishing perpetrators of consanguineous sexual relations. Furthermore, society should avoid this act, as it not only constitutes a major sin but also severely damages morals and mental well-being.